Dendritic field size and morphology of midget and parasol ganglion cells of the human retina. - Dacey, D M (1992)
The visual system of the macaque monkey has provided a useful model for understanding the neural basis of human vision, yet, there are few detailed comparisons of neural populations other than photoreceptors for the two species. Using intracellular staining in an in vitro preparation of the isolated and intact human retina, we have characterized the relationship of dendritic field size to retinal eccentricity for the two major ganglion cell classes, the midget and the parasol cells. We report three findings. (i) The difference in dendritic field diameter between the parasol and midget cells increases from a ratio of approximately 3:1 in the retinal periphery to approximately 10:1 at 3 degrees eccentricity, suggesting that human midget cells may outnumber parasol cells by as much as 30:1 in the central retina. (ii) The dendritic fields of human ON-center parasol and midget cells are 30-50% larger in diameter than their OFF-center counterparts, suggesting a distinct asymmetry in the human ON-OFF visual pathways. (iii) The dendritic fields of parasol cells, but not midget cells, are larger in humans than in macaques. The difference increases from approximately 20% in the retinal periphery to approximately 90% at 5 degrees eccentricity. This result predicts that the human parasol cells should show a lower resolving ability and an increased sensitivity to luminance contrast than their equivalents in the macaque.